Titanium nitride nanotube array material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611129177.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-28
AI Technical Summary
但该类改性手段存在固有缺陷:碳材料本身为非极性结构,与极性多硫化锂的相互作用力极弱,仅能依靠物理吸附固定多硫化物,吸附稳定性差,无法从根本上抑制多硫化物穿梭问题,改性效果十分有限
(1)本发明先通过一次氧化脱膜构建均匀凹坑基底,再二次氧化生长高度规整的TiO2纳米管阵列,最终原位氮化得到TiN纳米管阵列材料。该结构将高导电氮化钛骨架直接原位生长于钛集流体表面,彻底摒弃传统粉末电极的粘结剂、导电剂体系,消除界面接触电阻与粘结剂极化内阻。规整开放的三维管状孔道结构可实现硫活性物质的均匀负载,有效缓冲充放电体积膨胀,同时TiN的高导电性与丰富活性位点可加速多硫化物氧化还原动力学,最终赋予锂硫电池高放电比容量、优异倍率性能与长循环稳定性。
Smart Images

Figure CN122627384B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, specifically to a titanium nitride nanotube array material, its preparation method, and its application. Background Technology
[0002] Lithium-sulfur batteries, with their ultra-high theoretical specific capacity (1675 mAh / g) and energy density (2600 Wh / kg), along with their abundant sulfur resources, environmental friendliness, and low cost, have become one of the core candidates for next-generation high-energy-density electrochemical energy storage systems, showing broad application prospects in new energy storage and power batteries. However, the commercialization of lithium-sulfur batteries is currently constrained by many inherent technological bottlenecks, severely limiting their large-scale application. These specific problems manifest in the following three aspects: Firstly, the polysulfide shuttle effect. Soluble long-chain lithium polysulfides (Li₂S₂) are generated during the discharge process of the sulfur cathode. n (4≤n≤8), these intermediate products are highly soluble in battery ether electrolytes and diffuse to the lithium anode surface under the drive of concentration gradient, causing side reactions. This not only causes irreversible loss of positive electrode active material, but also corrodes the lithium anode, causes battery coulombic efficiency decay, and significantly shortens battery cycle life.
[0003] Secondly, the positive electrode volume expands dramatically. During the process of complete lithiation of elemental sulfur to form the final discharge product Li2S, the electrode volume expansion rate is as high as about 80%. The continuous volume deformation during repeated charging and discharging can easily lead to the collapse of the positive electrode structure and the shedding of active materials, resulting in rapid degradation of electrode performance and extremely poor stability.
[0004] Third, the electrode reaction kinetics are sluggish. Elemental sulfur and its end products Li2S and Li2S2 are both electronically and ionicly insulating materials. During charging and discharging, the charge transport resistance is high and the redox reaction rate is slow, which greatly restricts the rate performance and discharge capacity of lithium-sulfur batteries.
[0005] The current mainstream solution in the industry is to load sulfur-active substances onto conductive carbon materials such as carbon nanotubes, porous carbon, and graphene, relying on the high conductivity and porous structure of carbon materials to improve electrode conductivity and buffer volume expansion. However, this type of modification method has inherent defects: carbon materials themselves are non-polar structures, and the interaction force with polar lithium polysulfides is extremely weak. They can only rely on physical adsorption to fix polysulfides, resulting in poor adsorption stability and an inability to fundamentally suppress the polysulfide shuttle problem, thus the modification effect is very limited.
[0006] In recent years, transition metal nitrides (TiN, VN, Mo2N, etc.) have become a research hotspot for cathode host materials in lithium-sulfur batteries due to their excellent metalloid conductivity, stable chemical inertness, and unique polysulfide adsorption and catalytic activity. Among them, titanium nitride (TiN) has the best overall performance, possessing not only an ultra-low resistivity as low as 20 μΩ·cm and excellent structural and chemical stability, but also a strong chemical affinity for polar polysulfides. Its abundant active sites can form stable Ti-S chemical bonds with polysulfides, efficiently immobilizing polysulfides through chemical anchoring. At the same time, it can catalyze sulfur-based redox reactions and accelerate charge transport, making it an ideal sulfur host modification material for lithium-sulfur batteries.
[0007] Currently, most TiN materials prepared using existing technologies are in powder form. In practical applications, they need to be mixed with polymer binders and conductive agents to form a slurry, which is then coated onto the surface of a planar current collector to prepare the electrode. This traditional electrode preparation process has many structural drawbacks: the introduction of binders significantly increases the internal impedance of the electrode, reducing the battery's kinetic performance; the powdered TiN and the current collector are only physically bonded, resulting in weak interfacial bonding strength, making them prone to interfacial delamination during charge and discharge; at the same time, the powdered material lacks a regular and ordered pore structure, leading to uneven sulfur loading and agglomeration of active materials, which prevents the full utilization of TiN's conductivity, adsorption, and catalytic advantages, severely restricting further improvements in the electrochemical performance of lithium-sulfur batteries.
[0008] Therefore, developing a TiN electrode material that requires no binder, has an ordered and regular structure, and combines high conductivity with efficient polysulfide anchoring is of great engineering value and practical significance for breaking through the technological bottlenecks of lithium-sulfur batteries and promoting their commercialization. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the present invention aims to provide a titanium nitride nanotube array material, its preparation method, and its applications. The present invention uses a secondary anodizing process combined with nitriding to grow an ordered TiN nanotube array with uniform channels in situ on a pure titanium metal substrate. This structure can be directly used as a current collector and sulfur host material without the need for additional binders and conductive agents.
[0010] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a titanium nitride nanotube array material includes the following steps: S1. Preparation of pretreated titanium sheets Using pure titanium sheets as a substrate, physical polishing, ethanol degreasing, and electrolytic polishing were performed sequentially to obtain pretreated titanium sheets.
[0011] In this step, the specific steps for physical polishing are: mechanically polish the surface with 2000-grit sandpaper until it is smooth.
[0012] In this step, the specific steps for removing oil with ethanol are as follows: ultrasonic cleaning in anhydrous ethanol for 15-30 minutes at a power of 50-100W.
[0013] In this step, after the ethanol degreasing is completed, the product is rinsed with deionized water and then dried in a 60°C oven.
[0014] In this step, the specific process of electropolishing is as follows: using a titanium sheet as the anode and a stainless steel plate as the cathode, polishing is performed in an electropolishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes.
[0015] S2. Preparation of titanium sheets with pits on the surface Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, a first anodic oxidation treatment is performed in electrolyte A. Subsequently, the titanium oxide film generated by anodic oxidation is removed to obtain a titanium sheet with pits on its surface.
[0016] In this step, electrolyte A comprises the following components by weight: 0.25-0.5 parts ammonium fluoride, 2-5 parts water, and 100 parts ethylene glycol.
[0017] In this step, the voltage for the first anodizing treatment is 20-80V, the oxidation time is 2-8h, and the oxidation temperature is 15-20℃.
[0018] In this step, the titanium sheet after the first anodization is immersed in the removal solution (chromic acid: phosphoric acid = 1:1, volume ratio, 60℃) for 2 hours to remove the TiO2 film layer formed on the surface, leaving an ordered pit array. It is then washed three times alternately with deionized water and ethanol, and dried with nitrogen to obtain a titanium sheet with pits on the surface.
[0019] S3. Preparation of titanium sheets with a surface layer of titanium dioxide nanotube arrays. Using a titanium sheet with pitted surfaces as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B to obtain a titanium sheet with a titanium dioxide nanotube array on the surface.
[0020] In this step, electrolyte B comprises the following components by weight: 0.25-0.5 parts ammonium fluoride, 0.05-0.15 parts sodium tetrafluoroborate, 0.4-0.8 parts polyacrylic acid, 0.5-1 part urea, 15-20 parts dimethyl sulfoxide, 2-5 parts water, and 100 parts ethylene glycol.
[0021] In this step, the mass ratio of ammonium fluoride to sodium tetrafluoroborate is 3-5:1.
[0022] In this step, the voltage for the second anodizing treatment is 40-60V, the oxidation time is 3-6h, and the oxidation temperature is 5-10℃.
[0023] S4. Preparation of titanium nitride nanotube array materials Titanium sheets with a surface layer of titanium dioxide nanotube arrays are placed in a tubular reactor and nitrided under an ammonia atmosphere. After cooling, titanium nitride nanotube array material is obtained.
[0024] The specific steps of the nitriding treatment in this process are as follows: First, purge the reactor with nitrogen gas, then introduce pure ammonia gas, raise the temperature to 400-450℃ at a rate of 5-10℃ / min, hold for 2-3 hours, and then raise the temperature to 750-850℃ at a rate of 2-5℃ / min, and hold for 1-3 hours.
[0025] The present invention provides a titanium nitride nanotube array material prepared by the above preparation method.
[0026] The present invention also provides the application of the above-mentioned titanium nitride nanotube array material in the preparation of lithium-sulfur battery cathode materials.
[0027] Specifically, the titanium nitride nanotube array material is immersed in a sulfur-containing liquid impregnation solution, and after drying, sulfur is loaded into the channels and surface of the TiN nanotube array, thus obtaining the cathode material for lithium-sulfur batteries.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) In this invention, a uniform pitted substrate is first constructed through a single oxidation and demolding process, followed by a second oxidation process to grow a highly regular TiO2 nanotube array, and finally, TiN nanotube array material is obtained through in-situ nitriding. This structure directly grows a highly conductive titanium nitride framework in-situ on the surface of a titanium current collector, completely eliminating the binder and conductive agent system of traditional powder electrodes and eliminating interfacial contact resistance and binder polarization resistance. The regular and open three-dimensional tubular channel structure can achieve uniform loading of sulfur active materials, effectively buffering the volume expansion during charge and discharge. At the same time, the high conductivity and abundant active sites of TiN can accelerate the redox kinetics of polysulfides, ultimately endowing lithium-sulfur batteries with high discharge specific capacity, excellent rate performance and long cycle stability.
[0029] (2) This invention innovatively employs a dual-fluorine source composite system of ammonium fluoride / sodium tetrafluoroborate, avoiding the defects of excessively rapid etching and tube collapse caused by single ammonium fluoride etching. During the anodizing process, highly active F... - BF4 is responsible for rapidly etching longitudinally towards the bottom of the tube to form the tube, while its etching activity is milder and its dissociation rate is slower. - It can synergistically participate in the etching of tube wall and tube opening, balance the overall etching dynamics, suppress excessive dissolution of tube opening, tube wall perforation and uneven tube length, significantly improve the regularity and structural uniformity of nanotube array, and provide a stable and orderly structural substrate for subsequent in-situ nitriding modification and efficient loading of sulfur.
[0030] (3) In this invention, DMSO and polyacrylic acid are combined in electrolyte B for synergistic modification. The ethylene glycol organic system has sufficient polarity but high viscosity, resulting in high resistance to ion mass transfer within the confined channels of the nanotubes. The introduction of highly polar and low-viscosity DMSO reduces the viscosity of the mixed electrolyte system, significantly improving the migration rate and longitudinal mass transfer efficiency of fluoride ions in the narrow channels. At the same time, under the action of a strong electric field, the negatively charged long chains of polyacrylic acid polymer undergo directional electrophoretic migration, selectively adsorbing and coating the nanotube opening and the outer side of the tube wall, forming a stable surface adsorption protective layer, effectively inhibiting the lateral etching of the tube wall and the over-corrosion of the tube opening by fluoride ions. The synergistic effect of the two achieves rapid longitudinal directional tube formation and precise protection of lateral morphology, laying the foundation for the subsequent in-situ nitriding preparation of high-performance nanotube array materials. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the process flow for the titanium nitride nanotube array material provided by the present invention. Figure 2 The images shown are SEM images of the TiN materials prepared in Example 1 and Comparative Examples 1-4 of the present invention, wherein (a) is an SEM image of the material prepared in Example 1; (b) is an SEM image of the material prepared in Comparative Example 1; (c) is an SEM image of the material prepared in Comparative Example 2; (d) is an SEM image of the material prepared in Comparative Example 3; and (e) is an SEM image of the material prepared in Comparative Example 4. Figure 3 The energy spectrum of the TiN nanotube array prepared in Example 1 of this invention is shown. Figure 4 The image shows the XRD pattern of the TiN nanotube array prepared in Example 1 of this invention. Figure 5 This is a charge-discharge curve of the TiN-NTA / S composite cathode material prepared in Example 1 of the present invention; Figure 6 This is a 0.1 C long-cycle curve of the TiN-NTA / S composite cathode button cell prepared in Example 1 of the present invention. Detailed Implementation
[0032] The present invention will be further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0033] It should be noted that, unless otherwise specified, all chemical reagents involved in this invention were purchased through commercial channels.
[0034] The pure titanium sheet used in this embodiment of the invention has a size of 12mm×12mm and a thickness of 0.2mm.
[0035] Example 1 A method for preparing a titanium nitride nanotube array material includes the following steps: S1. Using pure titanium sheet as a substrate, first use 2000-grit sandpaper to mechanically polish until the surface is smooth, then ultrasonically clean in anhydrous ethanol for 15 minutes with an ultrasonic power of 100W. After the ethanol degreasing is completed, rinse with deionized water and dry in an oven at 60℃. Then, using the titanium sheet as the anode and the stainless steel plate as the cathode, polish in an electrolytic polishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes to obtain the pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, a first anodizing treatment is performed in electrolyte A, which includes the following components by weight: 0.25 parts ammonium fluoride, 2 parts water, and 100 parts ethylene glycol. The voltage for the first anodizing treatment is 30V, the oxidation time is 4h, and the oxidation temperature is 20℃. Subsequently, the titanium sheet after the first anodizing is immersed in a removal solution (chromic acid: phosphoric acid = 1:1, volume ratio, 60℃) for 2h to remove the TiO2 film layer formed on the surface. It is then washed three times alternately with deionized water and ethanol, and dried with nitrogen to obtain a titanium sheet with pits on the surface. S3. Using a titanium sheet with pitted surfaces as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B, which includes the following components by weight: 0.25 parts ammonium fluoride, 0.05 parts sodium tetrafluoroborate, 0.4 parts polyacrylic acid, 0.5 parts urea, 15 parts dimethyl sulfoxide, 2 parts water, and 100 parts ethylene glycol. The voltage for the second anodic oxidation treatment is 40V, the oxidation time is 6h, and the oxidation temperature is 10℃. Then, the sample is washed with deionized water, soaked in ethanol for 30 min, and air-dried naturally to obtain a titanium sheet with a titanium dioxide nanotube array on the surface. S4. Cut the titanium sheet with the surface layer of titanium dioxide nanotube array into round pieces (12 mm in diameter), place them in a quartz boat, load them into a tubular reactor, purge the reactor with nitrogen gas at 150 mL / min for 1 h, then introduce pure ammonia gas (NH3) at a flow rate of 100 mL / min, stabilize for 30 min, raise the temperature to 450 °C at 5 °C / min, hold the temperature for 2 h (maintain ammonia gas flow rate of 100 mL / min), raise the temperature to 800 °C at 2 °C / min, hold the temperature for 2 h, turn off the heating, allow the sample to cool naturally to room temperature, maintain the ammonia gas flow rate of 100 mL / min until it is below 200 °C, then switch to nitrogen gas, continue to purge with nitrogen gas overnight, remove the sample, and you will get the titanium nitride nanotube array material.
[0036] Example 2 A method for preparing a titanium nitride nanotube array material includes the following steps: S1. Using pure titanium sheet as a substrate, first use 2000-grit sandpaper to mechanically polish until the surface is smooth, then ultrasonically clean in anhydrous ethanol for 15 minutes with an ultrasonic power of 100W. After the ethanol degreasing is completed, rinse with deionized water and dry in an oven at 60℃. Then, using the titanium sheet as the anode and the stainless steel plate as the cathode, polish in an electrolytic polishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes to obtain the pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, a first anodizing treatment is performed in electrolyte A, which includes the following components by weight: 0.5 parts ammonium fluoride, 5 parts water, and 100 parts ethylene glycol. The voltage for the first anodizing treatment is 20V, the oxidation time is 8h, and the oxidation temperature is 20℃. Subsequently, the titanium sheet after the first anodizing is immersed in a removal solution (chromic acid: phosphoric acid = 1:1, volume ratio, 60℃) for 2h to remove the TiO2 film layer formed on the surface. It is then washed three times alternately with deionized water and ethanol, and dried with nitrogen to obtain a titanium sheet with pits on the surface. S3. Using a titanium sheet with pitted surfaces as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B, which includes the following components by weight: 0.45 parts ammonium fluoride, 0.15 parts sodium tetrafluoroborate, 0.8 parts polyacrylic acid, 1 part urea, 20 parts dimethyl sulfoxide, 5 parts water, and 100 parts ethylene glycol. The voltage for the second anodic oxidation treatment is 60V, the oxidation time is 3h, and the oxidation temperature is 10℃. Then, the sample is washed with deionized water, soaked in ethanol for 30 min, and air-dried naturally to obtain a titanium sheet with a titanium dioxide nanotube array on the surface. S4. Cut the titanium sheet with the surface layer of titanium dioxide nanotube array into round pieces (12 mm in diameter), place them in a quartz boat, load them into a tubular reactor, purge the reactor with nitrogen gas at 150 mL / min for 1 h, then introduce pure ammonia gas (NH3) at a flow rate of 100 mL / min, stabilize for 30 min, raise the temperature to 450 °C at 5 °C / min, hold the temperature for 2 h (maintain ammonia gas flow rate of 100 mL / min), raise the temperature to 800 °C at 2 °C / min, hold the temperature for 2 h, turn off the heating, allow the sample to cool naturally to room temperature, maintain the ammonia gas flow rate of 100 mL / min until it is below 200 °C, then switch to nitrogen gas, continue to purge with nitrogen gas overnight, remove the sample, and you will get the titanium nitride nanotube array material.
[0037] Example 3 A method for preparing a titanium nitride nanotube array material includes the following steps: S1. Using pure titanium sheet as a substrate, first use 2000-grit sandpaper to mechanically polish until the surface is smooth, then ultrasonically clean in anhydrous ethanol for 15 minutes with an ultrasonic power of 100W. After the ethanol degreasing is completed, rinse with deionized water and dry in an oven at 60℃. Then, using the titanium sheet as the anode and the stainless steel plate as the cathode, polish in an electrolytic polishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes to obtain the pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, a first anodizing treatment is performed in electrolyte A, which includes the following components by weight: 0.3 parts ammonium fluoride, 4 parts water, and 100 parts ethylene glycol. The voltage for the first anodizing treatment is 80V, the oxidation time is 2h, and the oxidation temperature is 20℃. Subsequently, the titanium sheet after the first anodizing is immersed in a removal solution (chromic acid: phosphoric acid = 1:1, volume ratio, 60℃) for 2h to remove the TiO2 film layer formed on the surface. It is then washed three times alternately with deionized water and ethanol, and dried with nitrogen to obtain a titanium sheet with pits on the surface. S3. Using a titanium sheet with pitted surfaces as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B, which includes the following components by weight: 0.5 parts ammonium fluoride, 0.1 parts sodium tetrafluoroborate, 0.6 parts polyacrylic acid, 0.8 parts urea, 18 parts dimethyl sulfoxide, 3 parts water, and 100 parts ethylene glycol. The voltage for the second anodic oxidation treatment is 60V, the oxidation time is 3h, and the oxidation temperature is 10℃. Then, the sample is washed with deionized water, soaked in ethanol for 30 min, and air-dried naturally to obtain a titanium sheet with a titanium dioxide nanotube array on the surface. S4. Cut the titanium sheet with the surface layer of titanium dioxide nanotube array into round pieces (12 mm in diameter), place them in a quartz boat, load them into a tubular reactor, purge the reactor with nitrogen gas at 150 mL / min for 1 h, then introduce pure ammonia gas (NH3) at a flow rate of 100 mL / min, stabilize for 30 min, raise the temperature to 450 °C at 5 °C / min, hold the temperature for 2 h (maintain ammonia gas flow rate of 100 mL / min), raise the temperature to 800 °C at 2 °C / min, hold the temperature for 2 h, turn off the heating, allow the sample to cool naturally to room temperature, maintain the ammonia gas flow rate of 100 mL / min until it is below 200 °C, then switch to nitrogen gas, continue to purge with nitrogen gas overnight, remove the sample, and you will get the titanium nitride nanotube array material.
[0038] Comparative Example 1 A method for preparing titanium nitride material includes the following steps: S1. Using pure titanium sheet as a substrate, first use 2000-grit sandpaper to mechanically polish until the surface is smooth, then ultrasonically clean in anhydrous ethanol for 15 minutes with an ultrasonic power of 100W. After the ethanol degreasing is completed, rinse with deionized water and dry in an oven at 60℃. Then, using the titanium sheet as the anode and the stainless steel plate as the cathode, polish in an electrolytic polishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes to obtain the pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, anodizing treatment is performed in electrolyte A, which includes the following components by weight: 0.25 parts ammonium fluoride, 2 parts water, and 100 parts ethylene glycol. The voltage for anodizing treatment is 30V, the oxidation time is 4h, and the oxidation temperature is 20℃. Then, the sample is washed with deionized water, soaked in ethanol for 30 min, and then air-dried to obtain a titanium sheet with titanium dioxide as the surface layer. S3. Cut titanium sheets with titanium dioxide as the surface layer into round pieces (12 mm in diameter), place them in a quartz boat, load them into a tubular reactor, purge the reactor with nitrogen gas at 150 mL / min for 1 hour, then introduce pure ammonia gas (NH3) at a flow rate of 100 mL / min, stabilize for 30 minutes, raise the temperature to 450℃ at 5℃ / min, hold the temperature for 2 hours (maintain ammonia gas flow rate of 100 mL / min), raise the temperature to 800℃ at 2℃ / min, hold the temperature for 2 hours, turn off the heating, allow the sample to cool naturally to room temperature, maintain the ammonia gas flow rate of 100 mL / min until it is below 200℃, then switch to nitrogen gas, continue to purge with nitrogen gas overnight, remove the sample, and you will get titanium nitride material.
[0039] Compared to Comparative Example 1 and Example 1, only the first anodizing treatment was performed.
[0040] Comparative Example 2 A method for preparing a titanium nitride nanotube array material includes the following steps: S1. Using pure titanium sheet as a substrate, first use 2000-grit sandpaper to mechanically polish until the surface is smooth, then ultrasonically clean in anhydrous ethanol for 15 minutes with an ultrasonic power of 100W. After the ethanol degreasing is completed, rinse with deionized water and dry in an oven at 60℃. Then, using the titanium sheet as the anode and the stainless steel plate as the cathode, polish in an electrolytic polishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes to obtain the pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, a first anodizing treatment is performed in electrolyte A, which includes the following components by weight: 0.25 parts ammonium fluoride, 2 parts water, and 100 parts ethylene glycol. The voltage for the first anodizing treatment is 30V, the oxidation time is 4h, and the oxidation temperature is 20℃. Subsequently, the titanium sheet after the first anodizing is immersed in a removal solution (chromic acid: phosphoric acid = 1:1, volume ratio, 60℃) for 2h to remove the TiO2 film layer formed on the surface. It is then washed three times alternately with deionized water and ethanol, and dried with nitrogen to obtain a titanium sheet with pits on the surface. S3. Using a titanium sheet with pitted surfaces as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B, which includes the following components by weight: 0.25 parts ammonium fluoride, 0.4 parts polyacrylic acid, 0.5 parts urea, 15 parts dimethyl sulfoxide, 2 parts water, and 100 parts ethylene glycol. The voltage for the second anodic oxidation treatment is 40V, the oxidation time is 6h, and the oxidation temperature is 10℃. Then, the sample is washed with deionized water, soaked in ethanol for 30 min, and air-dried naturally to obtain a titanium sheet with a titanium dioxide nanotube array on the surface. S4. Cut the titanium sheet with the surface layer of titanium dioxide nanotube array into round pieces (12 mm in diameter), place them in a quartz boat, load them into a tubular reactor, purge the reactor with nitrogen gas at 150 mL / min for 1 h, then introduce pure ammonia gas (NH3) at a flow rate of 100 mL / min, stabilize for 30 min, raise the temperature to 450 °C at 5 °C / min, hold the temperature for 2 h (maintain ammonia gas flow rate of 100 mL / min), raise the temperature to 800 °C at 2 °C / min, hold the temperature for 2 h, turn off the heating, allow the sample to cool naturally to room temperature, maintain the ammonia gas flow rate of 100 mL / min until it is below 200 °C, then switch to nitrogen gas, continue to purge with nitrogen gas overnight, remove the sample, and you will get the titanium nitride nanotube array material.
[0041] Compared to Comparative Example 2 and Example 1, no sodium tetrafluoroborate was added to electrolyte B.
[0042] Comparative Example 3 A method for preparing a titanium nitride nanotube array material includes the following steps: S1. Using pure titanium sheet as a substrate, first use 2000-grit sandpaper to mechanically polish until the surface is smooth, then ultrasonically clean in anhydrous ethanol for 15 minutes with an ultrasonic power of 100W. After the ethanol degreasing is completed, rinse with deionized water and dry in an oven at 60℃. Then, using the titanium sheet as the anode and the stainless steel plate as the cathode, polish in an electrolytic polishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes to obtain the pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, a first anodizing treatment is performed in electrolyte A, which includes the following components by weight: 0.25 parts ammonium fluoride, 2 parts water, and 100 parts ethylene glycol. The voltage for the first anodizing treatment is 30V, the oxidation time is 4h, and the oxidation temperature is 20℃. Subsequently, the titanium sheet after the first anodizing is immersed in a removal solution (chromic acid: phosphoric acid = 1:1, volume ratio, 60℃) for 2h to remove the TiO2 film layer formed on the surface. It is then washed three times alternately with deionized water and ethanol, and dried with nitrogen to obtain a titanium sheet with pits on the surface. S3. Using a titanium sheet with pitted surfaces as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B, which includes the following components by weight: 0.25 parts ammonium fluoride, 0.05 parts sodium tetrafluoroborate, 0.5 parts urea, 15 parts dimethyl sulfoxide, 2 parts water, and 100 parts ethylene glycol. The voltage for the second anodic oxidation treatment is 40V, the oxidation time is 6h, and the oxidation temperature is 10℃. Then, the sample is washed with deionized water, soaked in ethanol for 30 min, and air-dried naturally to obtain a titanium sheet with a titanium dioxide nanotube array on the surface. S4. Cut the titanium sheet with the surface layer of titanium dioxide nanotube array into round pieces (12 mm in diameter), place them in a quartz boat, load them into a tubular reactor, purge the reactor with nitrogen gas at 150 mL / min for 1 h, then introduce pure ammonia gas (NH3) at a flow rate of 100 mL / min, stabilize for 30 min, raise the temperature to 450 °C at 5 °C / min, hold the temperature for 2 h (maintain ammonia gas flow rate of 100 mL / min), raise the temperature to 800 °C at 2 °C / min, hold the temperature for 2 h, turn off the heating, allow the sample to cool naturally to room temperature, maintain the ammonia gas flow rate of 100 mL / min until it is below 200 °C, then switch to nitrogen gas, continue to purge with nitrogen gas overnight, remove the sample, and you will get the titanium nitride nanotube array material.
[0043] Compared to Comparative Example 3 and Example 1, no polyacrylic acid was added to electrolyte B.
[0044] Comparative Example 4 A method for preparing a titanium nitride nanotube array material includes the following steps: S1. Using pure titanium sheet as a substrate, first use 2000-grit sandpaper to mechanically polish until the surface is smooth, then ultrasonically clean in anhydrous ethanol for 15 minutes with an ultrasonic power of 100W. After the ethanol degreasing is completed, rinse with deionized water and dry in an oven at 60℃. Then, using the titanium sheet as the anode and the stainless steel plate as the cathode, polish in an electrolytic polishing solution (perchloric acid: ethylene glycol = 1:9, volume ratio) at a voltage of 30V and a temperature of 10℃ for 3 minutes to obtain the pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, a first anodizing treatment is performed in electrolyte A, which includes the following components by weight: 0.25 parts ammonium fluoride, 2 parts water, and 100 parts ethylene glycol. The voltage for the first anodizing treatment is 30V, the oxidation time is 4h, and the oxidation temperature is 20℃. Subsequently, the titanium sheet after the first anodizing is immersed in a removal solution (chromic acid: phosphoric acid = 1:1, volume ratio, 60℃) for 2h to remove the TiO2 film layer formed on the surface. It is then washed three times alternately with deionized water and ethanol, and dried with nitrogen to obtain a titanium sheet with pits on the surface. S3. Using a titanium sheet with pitted surfaces as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B, which includes the following components by weight: 0.25 parts ammonium fluoride, 0.05 parts sodium tetrafluoroborate, 0.4 parts polyacrylic acid, 0.5 parts urea, 2 parts water, and 100 parts ethylene glycol. The voltage for the second anodic oxidation treatment is 40V, the oxidation time is 6h, and the oxidation temperature is 10℃. Then, the sample is washed with deionized water, soaked in ethanol for 30 min, and air-dried naturally to obtain a titanium sheet with a titanium dioxide nanotube array on the surface. S4. Cut the titanium sheet with the surface layer of titanium dioxide nanotube array into round pieces (12 mm in diameter), place them in a quartz boat, load them into a tubular reactor, purge the reactor with nitrogen gas at 150 mL / min for 1 h, then introduce pure ammonia gas (NH3) at a flow rate of 100 mL / min, stabilize for 30 min, raise the temperature to 450 °C at 5 °C / min, hold the temperature for 2 h (maintain ammonia gas flow rate of 100 mL / min), raise the temperature to 800 °C at 2 °C / min, hold the temperature for 2 h, turn off the heating, allow the sample to cool naturally to room temperature, maintain the ammonia gas flow rate of 100 mL / min until it is below 200 °C, then switch to nitrogen gas, continue to purge with nitrogen gas overnight, remove the sample, and you will get the titanium nitride nanotube array material.
[0045] Compared to Comparative Example 4 and Example 1, no dimethyl sulfoxide was added to electrolyte B.
[0046] A schematic diagram of the process for the titanium nitride nanotube array material provided by this invention is shown below. Figure 1 As shown.
[0047] SEM images of the TiN materials prepared in Example 1 and Comparative Examples 1-4 of this invention are shown below. Figure 2 As shown in the figure, the titanium nitride prepared by this invention has a uniform and continuous nanoarray morphology, which is significantly better than the morphology of other comparative examples.
[0048] The energy spectrum of the TiN nanotube array prepared in Example 1 of this invention is as follows: Figure 3As shown in the image, the SEM on the left reveals a well-organized porous nanopore array structure, with Ti and N elements exhibiting continuous and uniform distribution, without localized elemental enrichment or deficiency. This result confirms that Ti and N elements are fully composited after high-temperature nitriding, the TiN nanoarray has a uniform composition, and the nitriding transformation is complete.
[0049] The XRD pattern of the TiN nanotube array prepared in Example 1 of this invention is as follows: Figure 4 As shown, the 2θ positions of the main diffraction peaks in the spectrum and their corresponding crystal planes are: 36.7° → TiN (111) crystal plane, 42.6° → TiN (200) crystal plane (strongest peak), 61.8° → TiN (220) crystal plane, 74.1° → TiN (311) crystal plane, and 78.0° → TiN (222) crystal plane. This conforms to the diffraction characteristics of face-centered cubic (FCC) TiN, proving that the synthesized TiN has a typical cubic crystal structure.
[0050] Using the TiN-NTA discs prepared in Examples 1-3 and Comparative Examples 1-4 of this invention as sulfur hosts, sulfur was loaded using a liquid-phase impregnation method. The specific steps are as follows: elemental sulfur (sublimed sulfur) was dissolved in CS2 to prepare a 10 mg / mL sulfur-CS2 solution. Then, the TiN-NTA discs were immersed in 50 mL of the above solution and soaked at room temperature for 12 h. After being removed, they were dried in a vacuum drying oven at 60 °C for 12 h to allow CS2 to volatilize and sulfur to be uniformly deposited in the pores of the TiN nanotubes. The above impregnation-drying process was repeated twice to further increase the sulfur loading and obtain the TiN-NTA / S composite cathode material.
[0051] Battery assembly: Positive electrode: The TiN-NTA / S composite positive electrode material prepared above is used as the working electrode, without the need to add binder and conductive agent; Negative electrode: Lithium metal sheet, 15mm in diameter and 0.6mm thick; Separator: Celgard 2400 polypropylene separator; Electrolyte: 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) dissolved in DOL:DME (1:1 vol%), with 2 wt% LiNO3 added; Assembly: CR2032 coin cells were assembled in an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm). Lithium metal sheets, TiN-NTA / S, and Celgard 2400 were used as the negative electrode, positive electrode, and separator, respectively. The electrolyte was a mixture of 1,2-dimethoxyethane (DME) and 1,3-dioxane (DOL) (V:V, 1:1), with electrolyte additives including 1.0 M lithium bis(trifluoromethane)sulfonylimide (LiTFSI) and 1.0 wt% LiNO3. The electrolyte volume was 25 μL·mg. -1 After the battery was assembled and allowed to stand for 12 hours for activation, its electrochemical performance was tested.
[0052] The assembled battery was tested using a Xinwei constant current charge-discharge tester. The charge-discharge test voltage window was 1.7-2.8V. The electrochemical performance test results are shown in Table 1.
[0053] Table 1 Electrochemical performance test results As can be seen from the table, compared with Comparative Examples 1-4, the TiN nanotube array materials prepared in the embodiments of the present invention have excellent electrochemical performance.
[0054] The charge-discharge curves of the TiN-NTA / S composite cathode material prepared in Example 1 of this invention are as follows: Figure 5 As shown in the figure, the electrode discharge curve exhibits two clear voltage plateaus at 2.35 V and 2.10 V, corresponding to the stepwise reduction process of polysulfides, with a discharge specific capacity reaching 1300 mAh·g. -1 The small polarization difference in the charge-discharge curves indicates that TiN-NTA can effectively catalyze the conversion of polysulfides and alleviate the shuttle effect, demonstrating excellent reversibility of the electrochemical reaction.
[0055] Figure 6 The figure shows the 0.1 C long-cycle curve of the TiN-NTA / S composite cathode button cell prepared in Example 1 of this invention. As can be seen from the figure, the initial specific capacity of this cathode reaches 1320 mAh·g at 0.1 C. -1 (Based on sulfur mass), it demonstrates a high utilization rate of elemental sulfur. After 200 cycles, the discharge specific capacity remains stable at approximately 1000 mAh·g. -1 The capacity decay rate is gradual throughout the cycle. An integrated TiN-NTA / S electrode replaces the traditional aluminum foil current collector; the TiN framework combines sulfur loading and current collection functions, significantly reducing interfacial resistance. This demonstrates that TiN-NTA can effectively suppress the shuttle effect by synergistically anchoring polysulfides through physical confinement and chemisorption, resulting in excellent long-cycle stability of the electrode.
[0056] Finally, it should be noted that the above embodiments do not limit the present invention in any way. Those skilled in the art can make modifications and improvements based on the present invention. Therefore, any modifications or improvements made without departing from the spirit of the present invention are within the scope of protection claimed by the present invention.
Claims
1. The application of a titanium nitride nanotube array material in the preparation of cathode materials for lithium-sulfur batteries, characterized in that, The preparation method of the lithium-sulfur battery cathode material is as follows: the titanium nitride nanotube array material is immersed in a sulfur-containing liquid phase impregnation solution, and after drying, sulfur is loaded in the channels and on the surface of the TiN nanotube array to obtain the lithium-sulfur battery cathode material. The preparation method of the titanium nitride nanotube array material is as follows: S1. Using pure titanium sheet as a substrate, physical polishing, ethanol degreasing and electrolytic polishing are performed sequentially to obtain a pretreated titanium sheet. S2. Using a pretreated titanium sheet as the anode and a platinum sheet as the cathode, the first anodic oxidation treatment is carried out in electrolyte A. Then, the titanium oxide film generated by anodic oxidation is removed to obtain a titanium sheet with pits on the surface. S3. Using a titanium sheet with pits on its surface as the anode and a platinum sheet as the cathode, a second anodic oxidation treatment is performed in electrolyte B to obtain a titanium sheet with a titanium dioxide nanotube array on its surface. S4. Place a titanium sheet with a titanium dioxide nanotube array on the surface in a tubular reactor and nitrid it under an ammonia atmosphere. After cooling, the titanium nitride nanotube array material is obtained. In step S2, electrolyte A comprises the following components by weight: 0.25-0.5 parts ammonium fluoride, 2-5 parts water, and 100 parts ethylene glycol. In step S3, electrolyte B comprises the following components by weight: 0.25-0.5 parts ammonium fluoride, 0.05-0.15 parts sodium tetrafluoroborate, 0.4-0.8 parts polyacrylic acid, 0.5-1 parts urea, 15-20 parts dimethyl sulfoxide, 2-5 parts water, and 100 parts ethylene glycol. In step S4, the specific steps of the nitriding treatment are as follows: First, purge the reactor with nitrogen gas, then introduce pure ammonia gas, raise the temperature to 400-450℃ at a heating rate of 5-10℃ / min, hold for 2-3 hours, and then raise the temperature to 750-850℃ at a heating rate of 2-5℃ / min, and hold for 1-3 hours.
2. The application according to claim 1, characterized in that, In step S2, the voltage for the first anodizing treatment is 20-80V, the oxidation time is 2-8h, and the oxidation temperature is 15-20℃.
3. The application according to claim 1, characterized in that, The mass ratio of ammonium fluoride to sodium tetrafluoroborate is 3-5:
1.
4. The application according to claim 1, characterized in that, In step S3, the voltage for the second anodizing treatment is 40-60V, the oxidation time is 3-6h, and the oxidation temperature is 5-10℃.